👤

Rozwiąż równanie:
a) (x-13)-(x - 5)+2x = 0,
c) x-(1-2x)+(x-3)=-4,
e) 5y-3.[7-(1-2y)]=0,
b) (5 - y)+(6-y)-(5 - y)=0,
d) (x+3) – 2x-(1-3x) = 2,
f) 1/5 • [4(x+2)+(3-x)]=4.
DAJE NAJJJ!!


Odpowiedź :

Odpowiedź:

a) (x-13)-(x - 5)+2x = 0

x-13-x+5+2x=0

-8+2x=0

2x=8

x=4

c) x-(1-2x)+(x-3)=-4

x-1+2x+x-3=-4

4x-4=-4

4x=0

x=0

e) 5y-3.[7-(1-2y)]=0

5y-3(6+2y)=0

5y-18-6y=0

-y-18=0

-y=18

y=-18

b) (5 - y)+(6-y)-(5 - y)=0

6-y=0

-y=-6

y=6

d) (x+3) – 2x-(1-3x) = 2

x+3-2x-1+3x=2

2x+2=2

2x=2

x=0

f) 1/5 • [4(x+2)+(3-x)]=4

4(x+2)+(2-x)=20

4x+8+3-x=20

3x+11=20

3x=20-11

3x=9

x=3

Szczegółowe wyjaśnienie:

Licze na naj

Odpowiedź:

Szczegółowe wyjaśnienie:

Zobacz obrazek PARASPARAS
Zobacz obrazek PARASPARAS
Zobacz obrazek PARASPARAS
Zobacz obrazek PARASPARAS